The role of potential oxidative biomarkers in the prognosis of intracerebral hemorrhage and the exploration antioxidants as possible preventive and treatment options - Yao, Jiayong; Dai, Xiaohong; Yv, Xueping; Zheng, Lei; Zheng, Jia; Kuang, Binglin; Teng, Wei; Yu, Weiwei; Li, Mingyue; Cao, Hongtao; Zou, Wei (Frontiers in Molecular Biosciences, 2025)
Intracerebral hemorrhage (ICH) is a non traumatic hemorrhage that occurs in a certain part of the brain. It usually leads to brain cell damage. According to a large number of experimental research, oxidative stress is an important pathophysiological processes of cerebral hemorrhage. In this paper, we aim to determine how changes in oxidative stress biomarkers indicate the damage degree of cerebral hemorrhage, and to explore and summarize potential treatments or interventions. We found that patients with cerebral hemorrhage are characterized by increased levels of oxidative stress markers, such as total malondialdehyde (MDA), F2 isoprostaglandin, hydroxynonenal, myeloperoxidase and protein hydroxyl. Therefore, the changes of oxidative stress caused by ICH on these markers can be used to evaluate and diagnose ICH, predict its prognosis, and guide preventive treatment to turn to antioxidant based treatment as a new treatment alternative.